A Comparison of Practices During the Confinement Period among Chinese, Malay, and Indian Mothers in Singapore. Issue 3 (27th March 2016) - Fok, Doris; Aris, Izzuddin M.; Ho, Jiahui; Lim, Sok Bee; Chua, Mei Chien; Pang, Wei Wei; Saw, Seang‐Mei; Kwek, Kenneth; Godfrey, Keith M.; Kramer, Michael S.; Chong, Yap Seng; ,
Abstract: Background: Confinement (restrictions placed on diet and practices during the month right after delivery) represents a key feature of Asian populations. Few studies, however, have focused specifically on ethnic differences in confinement practices. This study assesses the confinement practices of three ethnic groups in a multi‐ethnic Asian population. Methods: Participants were part of a prospective birth cohort study that recruited 1, 247 pregnant women (57.2% Chinese, 25.5% Malay, and 17.3% Indian) during their first trimester. The 1, 220 participants were followed up 3 weeks postpartum at home when questionnaires were administered to ascertain the frequency of adherence to the following confinement practices: showering; confinement‐specific meals; going out with or without the baby; choice of caregiver assistance; and the use of massage therapy. Results: Most participants reported that they followed confinement practices during the first 3 weeks postpartum (Chinese: 96.4%, Malay: 92.4%, Indian: 85.6%). Chinese and Indian mothers tended to eat more special confinement diets than Malay mothers ( p < 0.001), and Chinese mothers showered less and were more likely to depend on confinement nannies during this period than mothers from the two other ethnic groups ( p < 0.001 for all). Malay mothers tended to make greater use of massage therapy ( p < 0.001), whilst Indian mothers tended to have their mothers or mothers‐in‐law as assistant caregivers ( p < 0.001). Conclusion: Most Singapore mothers follow confinement practices, but the three Asian ethnic groups differed in specific confinement practices. Future studies should examine whether ethnic differences persist in later childrearing practices.